Daily Water Balance Analysis of the Sempor Reservoir in Central Java Using the SWAT Model for Operational Reliability Assessment - Ayu Septyandini Yudiva Putri; Asep Sapei; Chusnul Arif (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2026)
empor Reservoir plays a crucial role in supporting irrigation water supply, raw water provision, and flood control in Central Java. Effective reservoir operation requires reliable estimates of inflow and water availability to ensure sustainable water allocation under varying hydrological conditions. This study analyzes the daily water balance of Sempor Reservoir using the Soil and Water Assessment Tool (SWAT) model to simulate inflow and assess operational reliability. Daily rainfall and climate data for 2015–2024 were used, with streamflow observations used for model calibration (2015–2022) and validation (2023–2024). Model performance was evaluated using the Nash–Sutcliffe Efficiency (NSE) and the coefficient of determination (R2). The SWAT model performed very well, achieving NSE = 0.83 and R2 = 0.87. These performance statistics indicate that the simulated inflows closely matched the observed discharge and provide confidence in the model’s application for water balance analysis. Daily water balance results show that deficit conditions occur mainly during the dry season. Annual inflow and demand were 184.02 million m3 and 186.45 million m3, resulting in a deficit of 2.43 million m3. The reservoir was full for 36 days, sufficient for 311 days, and insufficient for 18 days, indicating approximately 95% reliability. Overall, the results demonstrate that the SWAT model is an effective tool for evaluating daily reservoir water balance and operational performance. The findings provide useful information for reservoir operation, water allocation planning, and sustainable water resources management under changing hydrological conditions. The results also provide valuable information for water managers in optimizing reservoir operation, improving water allocation efficiency, and reducing the impacts of seasonal water shortages.